Biology and systematics of gall-inducing triozids (Hemiptera: Psylloidea) associated with Psidium spp. (Myrtaceae) - Carneiro, Renê G.s.; Burckhardt, Daniel; Isaias, Rosy M.s. (Zootaxa, 2013)
Psidium myrtoides (Myrtaceae) shelters the gall inducer Nothotrioza myrtoidis gen. et sp. n. (Hemiptera: Psylloidea) which is described and illustrated here. Nothotrioza belongs to the family Triozidae and is probably most closely related to Neolithus, a monotypic Neotropical genus associated with Sapium (Euphorbiaceae). Three species are recognized with-in Nothotrioza: the type species N. myrtoidis sp. n. associated with Psidium myrtoides, N. cattleiani sp. n. (misidentified by Butignol & Pedrosa-Macedo as Neotrioza tavaresi) with Psidium cattleianum, and N. tavaresi (Crawford) comb. n. (from Neotrioza) with an unidentified species of Malpighiaceae, respectively. A lectotype is designated here for Neotrioza tavaresi. Also, the diversity of insect galls associated with P. myrtoides and the biology of N. myrtoidis were examined. N. myrtoidis presents five instars and an annual life cycle synchronised with the phenology of P. myrtoides. Gall size was proportional to the insect developmental stages, and rates of parasitism and mortality were 15.7 % and 29.8 %, respective-ly. The red colour is an important macroscopic diagnostic feature of the gall that could be associated with parasite-free condition of the galling insect. The biological features presented by the system Psidium myrtoides – Nothotrioza myrtoidis are in accordance with other systems involving sucking galling insects, however, it is exceptional by its univoltine life cycle associated with a perennial plant in the Neotropics. The galls induced by the three known Nothotrioza spp. are mor-phologically similar, i.e. closed, globoid and unilocular, as well as the opening mechanism for releasing the adults.